Uma proposta de procedimentos para identificar fraudes relevantes nas demonstrações contábeis - Vilaça, Leonardo Júnio (2012)
Relevant accounting frauds recorded in financial statements can result in material losses to the market and, as a result, to users of accounting information who employ the information to make their decisions. Recent facts have already showed that relevant frauds can result in material losses to the market and to accounting information users. Bankruptcies of huge American corporations such as Enron and WorldCom are some recent examples. In the global world that we live in today, where investors make transactions in different countries within seconds; information should be trustworthy and should show the reality of a company s business in accordance with the accounting rules in place. Management often has the incentive to commit relevant frauds in financial statements, such as pressure to meet results, lack of internal controls and lack of ethical behavior. In order to minimize fraud, companies should implement procedures that have the purpose to identify material frauds in their financial statements. These procedures should be implemented and monitored by competent, senior employees with strong professional skepticism. Although fraud is difficult to identify, companies should implement procedures to identify them in a timely manner and ensure that their financial statements are disclosed to the market and information users without material frauds